2022
DOI: 10.2147/cia.s365553
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Ischemic Stroke Patients Undergoing Endovascular Thrombectomy is Influenced by Systemic Inflammatory Index Through Malignant Brain Edema

Abstract: Purpose The systemic immune inflammatory index (SII), as a new marker, is widely used to predict the disease prognosis. We investigated the predictive value of SII for malignant cerebral edema (MCE) and whether postoperative MCE mediates the relationship between SII and functional prognosis in patients undergoing endovascular thrombectomy (EVT). Patients and Methods A total of 829 patients with anterior circulation large-vessel occlusive stroke (LVOS) were registered, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Another study found that SII of 444.77 can predict atrial fibrillation recurrence after ablation among diabetic patients 33 . In studies that included diabetic and non-diabetic patients, SII greater than 2140 could predict poor outcomes in stroke patients after endovascular thrombectomy 34 . Also, SII greater than 2120 was an independent risk factor of mortality among patients with ischemic stroke in another study 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that SII of 444.77 can predict atrial fibrillation recurrence after ablation among diabetic patients 33 . In studies that included diabetic and non-diabetic patients, SII greater than 2140 could predict poor outcomes in stroke patients after endovascular thrombectomy 34 . Also, SII greater than 2120 was an independent risk factor of mortality among patients with ischemic stroke in another study 35 .…”
Section: Discussionmentioning
confidence: 99%
“…(10) further identified that higher SII meant a greater risk of stroke severity and adverse clinical outcomes after AIS. Ji et al (24) identified elevated SII as related to malignant brain edema after EVT. Wang et al (25) findings further affirmed that SII was closely associated with the short-and long-term prognosis of patients with AIS, and higher SII were more likely to have poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation associated biomarkers such as monocyte and plateletcrit were reported to be associated with the development of cerebrovascular events including acute ischemic stroke (10,11). Recently, neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), neutrophil-albumin ratio (NAR), prognostic nutritional index (PNI), systemic immune inflammatory index (SII) and red cell distribution width (RDW) to albumin ratio (RA) have been reported as potential novel biomarkers of baseline inflammatory process and they were identified to be associated with the mortality of stroke (12)(13)(14)(15)(16)(17). These studies mainly explored the associations between these inflammation biomarkers and all stroke patients or ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 99%